Field efficacy of phytoextracts, antagonists and chemical fungicides with native approach for controlling banded leaf and sheath blight in maize - Subedi, Subash; Neupane, Saraswati; Oli, Lokendra; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2022)
Experiments on maize (Zea mays L.) were carried out aiming to control banded leaf and sheath blight (BLSB) caused by fungus, Rhizoctonia solani Kuhn with six treatments represented by different fungicides, antagonists and phytoextracts against control receiving no spray with three replicates of each under field conditions during two consecutive years from 2019 to 2020. In 2019, the higher Percent Disease Control (44.85%) and Percent Yield Increase (62.10%) both were estimated in plot treated with SAAF (carbendazim 12% WP + mancozeb 63% WP) followed by the plot where seed was treated with bavistin (carbendazim 50% WP). The grain yield was higher in plots treated with SAAF followed by leaf stripping method. Almost similar trends of disease control were observed in 2020. The lower percent disease index (47.67% PDI) with higher yield (4660 kg/ha) was recorded from the plot sprayed with SAAF@3 g/L during knee high and subsequent spray after 15 days interval followed by leaf stripping technique (lower 3-4 leaves from ground surface) as compared to control plot (PDI- 93.67% and yield-1393.33 kg/ ha). The results showed that, the combined treatment with fungicides i.e. seed treatment with bavistin before sowing and twice spraying of SAAF during knee height stage at 15 days interval followed by leaf stripping technique were effective to control banded leaf and sheath blight disease of maize to increase the yield.